The mystery of Medea: the original meaning of the character in literature and cinema - Fernández Gómez, Encarnación (Amaltea. Revista de Mitocrítica, 2024)
Within cinematographic art – unlike literary art – the character of Medea has been brought to the screen in the absence of condemnatory meanings of a moral nature. The primordial essence of the myth of Medea in the cinema is presented unrelated to the philosophical, scientific and rational point of view, since its ultimate meaning escapes even the literary language itself. Certainly, the most outstanding cinematographic creators have given life to this mythological figure in relation to the ineffable, that is, as an imaginary archetype that produces meaning: united with the symbolic, the silence, mystery and art.